Occurrence and fate of an emerging drug pollutant and its by-products during conventional and advanced wastewater treatment: Case study of furosemide. (May 2023) - Sandre, Fidji; Huynh, Nina; Caupos, Emilie; El-Mrabet, Lamyae; Partibane, Chandirane; Lachaise, Isabelle; Pommier, Christophe; Rivard, Michael; Morin, Christophe; Moilleron, Régis; Le Roux, Julien; Garrigue-Antar, Laure
Abstract: Conventional wastewater treatment systems are not designed to remove pharmaceutical compounds from wastewater. These compounds can be degraded into many other transformation products which are hardly, if at all, studied. In this context, we studied the occurrence and degradation of furosemide, a very frequently detected diuretic, along with its known degradation products in several types of wastewater. Influent and effluent from the Seine-Centre Wastewater Treatment Plant (WWTP) (Paris, France) as well as outlet of residential care homes (Dordogne, France) were analyzed by Ultra-Performance Liquid Chromatography-tandem Mass Spectrometry (UPLC-MS/MS) to quantify furosemide and its known degradation products, saluamine and pyridinium of furosemide. Oxidation experiments (chlorination, ozonation and UV photolysis with hydrogen peroxide) were then performed on furosemide solutions and on water from residential care facilities to study the degradation of furosemide by potential advanced processes, and also to identify unknown oxidation products by high-resolution mass spectrometry. Furosemide was well degraded in Seine-Centre WWTP (>75%) but did not increase the concentrations of its main degradation products. Saluamine and pyridinium of furosemide were already present at similar concentrations to furosemide in the raw wastewater (∼2.5–3.5 μg.L −1 ), and their removal in the WWTPs were very high (>80%). Despite their removal, the three compounds remained present in treated wastewater effluents at concentrations of hundreds of nanograms per liter. Chlorination degraded furosemide without pyridinium production unlike the other two processes. Chlorination and ozonation were also effective for the removal of furosemide and pyridinium in residential care home water, but they resulted in the production of saluamine. To our knowledge this is the first evidence of saluamine and pyridinium of furosemide in real water samples in either the particulate or dissolved phase. Graphical abstract: Image 1 Highlights: Pyridinium of furosemide and saluamine were quantified for the first time in wastewater samples. Seine-Centre WWTP shows a good removal of furosemide and its degradation products. Ozonation and chlorination completely degrade furosemide but may produce saluamine. New chlorination and UV/H2 O2 degradation products of furosemide were identified.